Replication of Standardized ADOS Domain Scores in the Simons Simplex Collection - Vanessa H. Bal; Catherine Lord (2015)
Raw totals from diagnostic and screening measures for autism spectrum disorder (ASD) are frequently used as dimensional measures of autism symptom severity without appropriate correction for confounding factors, such as developmental level or non‐ASD‐specific behavior problems. Although these associated features are important to consider when diagnosing ASD and developing intervention plans, both researchers and clinicians sometimes need metrics of ASD severity that are not influenced by these factors. The Autism Diagnostic Observation Schedule (ADOS) domain calibrated severity scores (CSS) were created to provide separate estimates of social affect (SA‐CSS) and restricted, repetitive behaviors (RRB‐CSS) that are relatively independent of child characteristics (Hus et al., 2014). Using a sample of 2,509 probands with ASD from the Simons Simplex Collection (SSC), this study provides the first replication of the ADOS domain CSS in an independent sample. Consistent with the original standardization study, when applied to existing SSC data, the ADOS domain CSS were less influenced by age and cognitive ability compared to raw domain totals. Domain CSS were also relatively independent of behavior problems. Use of the ADOS domain CSS to assess relationships between ASD symptoms and genetic risk factors will increase confidence that associations reflect domain‐specific relationships. Scores also offer less developmentally‐influenced estimates of ASD severity for future phenotypic explorations in the SSC. This independent replication provides support for the application of the ADOS domain CSS in other samples, though further replication in population‐based samples will be an important next step. Autism Res 2015, 8: 583–592 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.